Principio de Proporcionalidad de la pena en sentencias dictadas en delitos cometidos por menores de edad en Riobamba. - Carrasco Tite, Dayana Mishel (2025)
This study examines the principle of proportionality in sentencing minors for crimes in Riobamba. It reviews existing legislation and explores the potential for reform to equate the penal treatment of adolescents with that of adults. The research investigates the correlation between proportional sentences and recidivism in juvenile delinquency, proposing increased penalties for specific crimes as a deterrent. It suggests that harsher sanctions could send a strong message about the consequences of criminal behavior, thus promoting a fairer and more effective application of the principle of proportionality in sentencing. The study also considers the legal and social implications of possible changes to the juvenile justice system.